Predictors of Satisfaction With Work Environment in the Context of a Mismatch in Working Hours: A Nationwide, Large-Scale, Cross-Sectional Study - Robert Kim (SAGE Publishing, 2022)
This nationwide, large-scale, cross-sectional study has hypothesized that there might be differences in workers' satisfaction with work environment depending on demographic, socio-economic, and work characteristics in the context of a mismatch between actual and preferred working hours. The current study is a secondary data analysis of the Fifth Korean Working Conditions Survey. A total of 29 694 subjects (n = 29 694) were finally included in the current study. Female gender (β = −.372, OR 0.689 [95% CI 0.646-0.736]), age of ≥60 years old (β = .226, OR 1.253 [95% CI 1.089-1.441]), graduation from middle school (β = −.320, OR 0.726 [95% CI 0.616-0.856]), college (β = .492, OR 1.636 [95% CI 1.371-1.952]), or university (β = .826, OR 2.283 [95% CI 1.918-2.718]), fixed period of work (β = −.105, OR 0.901 [95% CI 0.823-0.986]), full-time employment (β = −.105, OR 0.900 [95% CI 0.813-0.996]), the engagement in public sector (β = .544, OR 1.722 [95% CI 1.532-1.935]), private-public partnership organization (β = .605, OR 1.832 [95% CI 1.342-2.500]) or NPO or NGO (β = .780, OR 2.182 [95% CI 1.522-3.127]), regular side job (β = −.929, OR 0.395 [95% CI 0.289-0.539]), or temporary side job (β = −.330, OR 0.719 [95% CI 0.533-0.970]), membership of multiple teams (β = −.501, OR 0.606 [95% CI 0.552-0.666]), labor union (β = .143, OR 1.154 [95% CI 1.047-1.273]), and better health status (β = .977, OR 2.657 [95% CI 1.175-6.007]) were predictors of satisfaction with work environment in the context of a mismatch between actual and desired working hours. Based on the current results, it can be concluded that female gender, age of ≥60 years old, graduation from middle school, college, or university, fixed period of work, full-time employment, the engagement in public sector, private-public partnership organization or NPO or NGO, regular side job or temporary side job, membership of multiple teams, labor union, and better health status were predictors of satisfaction with work environment.